Guideline for translation and national validation of the Quality of Life in Hand Eczema Questionnaire (QOLHEQ) - Oosterhaven, Jart; Diepgen, Thomas L.; Ofenloch, Robert (Contact dermatitis, 2017)
There is a need for well-developed and validated questionnaires to measure patient reported outcomes. The Quality of Life in Hand Eczema Questionnaire (QOLHEQ) is such a validated instrument measuring disease-specific health-related quality of life in hand eczema patients. A re-validation of measurement properties is required before an instrument is used in a new population. With the objective of arriving at a guideline for translation and national validation of the QOLHEQ, we have developed the design of a reference study on how to adequately assess measurement properties of the QOLHEQ based on interdisciplinary discussions and current standards. We present a step-by-step guideline to assess translation (including cross-cultural adaptation), scale structure, validity, reproducibility, responsiveness, and interpretability. We describe which outcomes should be reported for each measurement property, and give advice on how to calculate these. It is also specified which sample size is needed, how to deal with missing data, and which cutoff values should be applied for the measurement properties assessed during the validation process. In conclusion, this guideline, presenting a reference validation study for the QOLHEQ, creates the possibility to harmonize the national validation of the various language versions of the QOLHEQ.